Right ventricular dysfunction and injury following marathon running: Correlating biomarkers with cardiac MRI - Mousavi, N.; Czarnecki, A.; Kumar, K.; Fallah-Rad, N.; Lytwyn, M.; Han, S. -Y.; Francis, A.; Kirkpatrick, I. D. C.; Neilan, T. G.; Sharma, S.; Jassal, D. S. (2009)
Can too much exercise be detrimental to your health? Physical fitness has been shown to be an independent, long-term predictor of reduced morbidity and mortality from cardiovascular causes. Although the cardiovascular benefits of moderate exercise are well established, the cardiovascular effects of prolonged exertion, including marathon running, are less clear. Even though the risk of sudden death associated with participation in marathons is small, participation in such events is consistently associated with biochemical evidence of heart damage and dysfunction. The purpose of this study was to demonstrate the cardiac changes associated with participation in a marathon using serial cardiac biomarkers, echocardiography and CMR.